PENERAPAN PSAK NO. 45 PADA LAPORAN KEUANGAN YAYASAN HIMMATUN AYAT SURABAYA. - Bestari, Teguh Kristanti Laksmi; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research starts from the development of non-profit institutions in Indonesia that is the transparency of financial institution demands aconsistentand comparable standardof recording and reporting, it has been expected that by implementing the PSAK No. 45 the institution can process the financial information more professional and more qualified. The purpose of this research is to find out whether the presentation of the financial statements of Yayasan Himmatun Ayat Surabaya on the PSAK No. 45 and to find out whether the PSAK No.45 can be implemented competelyon thepreparation ofthe financial statements ofthe Yayasan Himmatun Ayat Surabaya.This research applies descriptive qualitative in which its purpose is to disclosure the real condition and fact onYayasan Himmatun Ayat Surabaya in the presentationof thefinancial statements whetherit hasmetthe standard of financial statement which is in accord with the PSAK No. 45 i.e.: the statements of financial position, the statements of activity, the statement of cash flow, and the recording of the financial statements. Based on the result of the research,it has been found that the Yayasan Himmatun Ayat Surabaya has notimplementedthe PSAK 45 yet and it is cannot be implemented completely on this foundation, since there is a problem with the human resources which is in the comprehension process of the financial statements, so the implementation takes more time tobe processed. The researcher recommends that the foundation should change the standard of preparation of financial statements so it can be in accord with the existing financial standard in Indonesia. Since the human resources have not got the skill in this field, training should be given to them in order to improve their capacity in the preparation of financial statement which is in accord with the standard.Keywords: Standard of Reporting, Statement of Financial Position, Statement of Activity, Statement of Cash Flow.